Measures of oral health-related quality of life in patients with bone graft and implant prosthetic rehabilitation at the anterior of mandible/maxilla among young and middle-aged adults: a retrospective pilot study - Kazuyuki Yusa; Shigeo Ishikawa; Nagiko Suzuki; Shunsuke Kunii; Naoki Okuyama; Tomoharu Hemmi; Mitsuyoshi Iino (SpringerOpen, 2023)
Abstract Objectives Dental implants are believed to contribute to improved masticatory function and oral health-related quality of life (OHRQOL), but the details remain unclear. The aim of this study was to evaluate the clinical outcomes of dental implant prosthetic rehabilitation after bone graft at the anterior mandible/maxilla based on OHRQOL, particularly in young and middle-aged patients. Methods This retrospective study included 11 patients who received bone grafts at the anterior mandible/maxilla and dental implant surgery. Chewing function score and OHRQOL (using the Oral Health Impact Profile-14 questionnaire) were evaluated before and after completion of an implant-retained bridge or removable implant-supported denture. Results Chewing function score tended to improve slightly after dental implant prosthetic rehabilitation, but none of the observed differences were significant. In the assessment of OHRQOL, relatively worse domain scores before completion of dental implant prosthetic rehabilitation were seen for Functional limitation, Psychological discomfort, and Psychological disability. Conversely, Social disability seemed relatively unaffected by tooth loss. All domain scores and total scores for items other than Physical disability and Social disability were significantly improved after completion of dental implant rehabilitation. Conclusions Tooth loss in the anterior region may not significantly affect chewing function score, but can have a significant impact on OHRQOL. Bone grafts and dental implant prosthetic rehabilitation can resolve these problems, and the results of this study will benefit both patients and medical professionals in terms of treatment planning and informed consent.